A new species of Tribonium Saussure, 1862 from the Province of Misiones, Argentina (Blattaria, Blaberidae, Zetoborinae) - Crespo, Francisco Antonio; Valverde, Alejandra Del Carmen; Iglesias, Mónica Sandra (Zootaxa, 2015)
Tribonium rothi sp. n. is described from Argentina, whereas T. neospectrum and T. conspersum are recorded for the first time for that country, and their genitalia is redescribed. Femur and tibial spine armature are given and Tribonium is compared with Schistopeltis. A key to identify species of the genus Tribonium recorded in Argentina is provided.